2018
DOI: 10.1002/jlb.2ma0517-190rr
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal peptide moiety of the Mycobacterium tuberculosis 19 kDa lipoprotein harbors RP105-agonistic properties

Abstract: Radioprotective 105 kDa (RP105, CD180) is a member of the Toll-like receptor (TLR) family that interacts with TLR2 and facilitates recognition of mature lipoproteins expressed by Mycobacterium tuberculosis and Mycobacterium bovis BCG. In this study, we used synthetic lipopeptide analogs of the M. tuberculosis 19 kDa lipoprotein to define structural characteristics that promote RP105-mediated host cell responses. A tripalmitoylated lipopeptide composed of the first 16 N-terminal amino acids of the M. tuberculos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…The Pam 3 CSS scaffold has been used along with the 16 N-terminal amino acids of the M. tuberculosis 19 kDa lipoprotein to give Pam 3 CSSNKSTTGSGETTTA which has been shown to be an agonist of RP105, a member of the TLR family that interacts with TLR2 and facilitates recognition of mature lipoproteins expressed by mycobacteria. 113 Mono- and dipalmityol analogues were also examined, as were peptide variants. These studies showed that, although the lipid moiety is required for macrophage activation, it is not a determinant of RP105 dependency.…”
Section: Toll-like Receptor Agonist Lipopeptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pam 3 CSS scaffold has been used along with the 16 N-terminal amino acids of the M. tuberculosis 19 kDa lipoprotein to give Pam 3 CSSNKSTTGSGETTTA which has been shown to be an agonist of RP105, a member of the TLR family that interacts with TLR2 and facilitates recognition of mature lipoproteins expressed by mycobacteria. 113 Mono- and dipalmityol analogues were also examined, as were peptide variants. These studies showed that, although the lipid moiety is required for macrophage activation, it is not a determinant of RP105 dependency.…”
Section: Toll-like Receptor Agonist Lipopeptidesmentioning
confidence: 99%
“…However, substitution of the T7 and T8 residues with nonpolar alanine residues led to reduced RP105 dependency. 113 …”
Section: Toll-like Receptor Agonist Lipopeptidesmentioning
confidence: 99%
“…Mycobacterial LPS lacks the teichoic acid residue present in the LPS of gram-positive and gram-negative bacteria. A recent report suggested that in lipoproteins such as the 19-kDa lipoprotein of Mycobacterium tuberculosis , the position of non-polar alanine residues but not the lipid moiety determines RP105 dependency ( Schultz et al, 2018 ). This expands our understanding of the ligands of RP105 and also indicates that this receptor recognizes lipid PAMPs via numerous mechanisms.…”
Section: Rp105: An Unconventional Members Of the Tlr Familymentioning
confidence: 99%
“…Mycobacterium tuberculosis lipopeptide ligands stimulate RP105 on macrophages and induce RP105-dependent TNF-α and IL-6 production by macrophages. Moreover, di- and tripalmitoylated variants of this lipopeptide can elicit an equivalent RP105-dependent response, indicating that the lipid moiety is required for macrophage activation but this event is RP105-independent ( Schultz et al, 2018 ). RP105 is a key determinant of macrophage activation in Mycobacterium tuberculosis infection.…”
Section: Rp105 and Osteoclastogenesismentioning
confidence: 99%
See 1 more Smart Citation